Implementasi Sistem Kontrol Suhu dan Kelembaban Gudang Penyimpanan Biji Kopi menggunakan Arduino Uno dan Protokol MQTT - Rahadian Sayogo; Mochammad Hannats Hanafi Ichsan; Rizal Maulana (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
In 2010 - 2014 the agricultural sector occupied the first position in terms of non-oil and gas exports in Indonesia, it explained that the Indonesian agricultural sector greatly supports the country's economy. One of the results of the agricultural sector is coffee plants that have been recognized by the global market as evidenced by occupying the fourth position in international coffee exports. The number and quality of Indonesian coffee caused Indonesia's coffee exports to rank fourth after Brazil, Vietnam and Thailand. Because 90% of coffee farmers in Indonesia who play a role are small-scale farmers who have agricultural areas between 1-2 hectares and coffee requires temperatures between 20 â„ƒ - 28 â„ƒ and humidity between 50% - 70% so that the flavor and quality of coffee produced is satisfying. That is why Indonesian coffee production is not optimal because it lags behind in terms of good coffee processing and technology from other countries. Therefore, to help small-scale coffee farmers in terms of increasing the quality of coffee production, a temperature and humidity control system for coffee bean storage is made using Arduino UNO and the MQTT protocol. The purpose of this system is to detect changes in the temperature and humidity of the coffee bean storage warehouse if the condition exceeds the system parameter point by automatically stabilizing it so that it does not damage the quality of the coffee.